Inclusive education, perspective from evaluation: Evolution in Colombian public policies - Barragán Moreno, Sandra Patricia; Marcelo Escalante, Eliacid (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work aims to visualize the evolution of the evaluation of the level of academic student achievement in Colombian public policies from 1968 to 2020, considering the closing of social, economic, and educational gaps that enable peaceful coexistence, respect for human rights and genuine inclusion. A mixed methodology was used to identify the evaluation progression from a summative result to a training and meaningful approach, and the results are distant from the goals of public policies that seek to bring Colombian students closer to a better quality of life.